Evolution of RANO in Assessing Brain Tumour Outcomes - Qurat-ul-Ain Virani; Zanib Javed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Assessing treatment response is extremely important in management of brain tumours. Response assessment in neuro-oncology (RANO) was introduced in 2008 for the purpose of making recommendations for it by addressing and countering the limitations in previously reported response criteriae. Subsequently, multiple RANO working groups have been formed to cater to different tumour types and to update their previous recommendations to counter the limitations in their criteria. Herein we have a summarized list of RANO criteria for adult brain tumours. Keywords: RANO, neuro-oncology, brain tumour, outcome